PEMANFAATAN TEKNIK MIND MAPPING SEBAGAI KERANGKA KARANGAN DALAM MENINGKATKAN KEMAMPUAN MENULIS KARANGAN PERSUASI SISWA KELAS X SMA NEGERI 2 KABUPATEN PINRANG - Rusman Latif (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Utilization of Mind Mapping technique as a Framework for Improving Writing Ability Essays in Persuasion Writing Class X SMAN 2 Pinrang. This study aimed to describe no significant difference persuasive essay writing using mind mapping techniques with no use of mind mapping technique as the outline of the class X SMAN 2 Pinrang. Design or research models used in this research is the study design is preeksperimental kind of design pretest and posttest group. Teknik used to collect the data of this study is the testing techniques. Data collected in the study were analyzed using descriptive statistical techniques t test types. The results of this study indicate that there are significant differences persuasive essay writing using mind mapping techniques with no use of mind mapping technique as the outline of the class X SMAN 2 Pinrang. Comparison of the ability of pretest and posttest results showed that as many as 9.29 t count> t table value of 2.04. This shows that the hypothesis proposed is accepted, that there are significant differences apaka write persuasive essays using mind mapping technique as the outline of the class X SMAN 2 Pinrang.